Performance-enhanced collagen sponge and preparation method thereof

Through optimized dialysis process and irradiation crosslinking technology, combined with lyophilization molding technology, collagen sponges with enhanced mechanical properties and water absorption characteristics were prepared, which solved the shortcomings of existing collagen sponges in terms of mechanical strength and biocompatibility, and achieved better cell tissue growth and material stability.

CN119909221AActive Publication Date: 2025-05-02TIANJIN SHI JI KANG TAI BIOMEDICAL ENG CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510416595.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-03
Publication Date
2025-05-02
Estimated Expiration
2045-04-03

AI Technical Summary

Technical Problem

Existing collagen sponges have shortcomings in mechanical strength and biocompatibility, especially in water absorption and cell tissue growth, resulting in failure of implantation.

Method used

The collagen gel matrix was prepared by an optimized dialysis process, and the glycerin was compounded into a homogeneous solution system. Then, the molecular cross-linking reaction was initiated by irradiation, and a collagen sponge with enhanced mechanical properties and water absorption was prepared in combination with lyophilization molding technology.

Benefits of technology

The mechanical strength of collagen sponge is improved and the water absorption is improved, and the formation of a "dry core" is avoided inside the material, which is conducive to the growth of cells into the material and delays the degradation of the material in the body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119909221A_ABST
    Figure CN119909221A_ABST
Patent Text Reader

Abstract

The invention provides a performance-enhanced collagen sponge and a preparation method thereof.The preparation method comprises the steps that firstly, collagen gel is prepared through an improved dialysis technology, then the collagen gel and glycerin are compounded to form a collagen solution, then the solution is treated through an irradiation crosslinking technology, and after vacuum freeze drying, a finished product is finally prepared through irradiation sterilization. The product is not dissolved by acid and is directly dialyzed, and a low-concentration phosphate buffer solution is subsequently adopted for dialysis, so that the pH value of the dialysis solution can be quickly adjusted to be neutral, and the production cycle of the dialysis process is greatly shortened; in addition, dialysis is performed by adopting a low-concentration phosphate buffer solution, and an irradiation cross-linking process is combined, so that on the premise of ensuring the mechanical strength of the product, the rehydration speed is high, 'dry cores' are prevented from being formed in the material, and cells can grow into the material favorably; a certain amount of glycerol is added into the formula of the collagen solution before irradiation crosslinking, so that shrinkage and deformation of the collagen after irradiation crosslinking can be avoided, and the size change of the product is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the category of medical products and relates to a performance-enhanced collagen sponge and a preparation method thereof. The product can be used in the fields of plastic surgery, dentistry, general surgery, etc., and is mainly used for hemostasis and regeneration repair of soft tissue injuries. Background Art

[0002] Collagen is an important bioregenerative material with the characteristics of low immunogenicity, biodegradability and promotion of tissue repair. It has been processed into powder, sponge or film and applied to the repair of soft and hard tissue injuries. Among them, collagen sponge is particularly common. It can be used in plastic surgery, general surgery, dermatology, trauma orthopedics and other fields, and has the effect of hemostasis and regeneration. At present, collagen sponge is mainly extracted from animal tissues such as bovine Achilles tendon, cowhide, pig skin, etc., or humanized collagen is prepared by genetic engineering technology, and then the collagen is prepared into a solution of a certain concentration and made into a porous sponge by vacuum freeze drying. The porous structure is conducive to the absorption of blood or exudate, and provides a three-dimensional scaffold for tissue regeneration and repair.

[0003] As a scaffold for tissue regeneration and repair, collagen sponge is required to have a certain mechanical support, that is, it can provide space for cells and tissues to grow in within a short period of time after implantation in the body; however, natural collagen sponge has poor mechanical strength and degrades too quickly. After cross-linking with glutaraldehyde or carbodiimide cross-linking agents (EDC / NHS), although the mechanical strength can be improved, the biocompatibility and hydrophilicity of the material become poor, especially for collagen sponge models with a certain thickness, such as plug-shaped and cylindrical ones. This type of product is generally used for filling, hemostasis and repair of tooth extraction sockets. Cross-linked products absorb water very slowly after implantation, and blood or body fluids penetrate into the material, which can easily lead to a lack of blood supply to the material, difficulty in the growth of cell tissues, and even cause the material to form granulomas after a certain period of implantation, ultimately leading to implantation failure. Therefore, there is an urgent need for a collagen sponge with high mechanical strength, good support, fast rehydration, good biocompatibility, and easy growth of cell tissues to solve the above technical problems.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The present invention provides a performance-enhanced collagen sponge and a preparation method thereof. The collagen gel matrix is ​​prepared by an optimized dialysis process, and glycerol is compounded to form a homogeneous solution system. Subsequently, a molecular cross-linking reaction is initiated by radiation. Finally, a collagen sponge material with enhanced mechanical properties and water absorption characteristics is successfully prepared in combination with freeze-drying molding technology. The present invention can quickly adjust the pH value of the dialysis solution to neutrality, greatly shortening the production cycle of the dialysis process. Under the premise of ensuring the mechanical strength of the product, the rehydration is fast and the formation of a "dry core" inside the material is avoided, which is conducive to the growth of cells into the material. The shrinkage and deformation of collagen after radiation cross-linking can be avoided, and the change in product size can be reduced. The present invention has broad application prospects and is conducive to popularization and application.

[0006] The present invention provides a method for preparing a performance-enhanced collagen sponge, comprising the following steps: S1: Dialysis: dialyze the collagen raw material using water for injection and phosphate buffer until the pH of the solution reaches above 6.0; S2: cross-linking, taking the collagen sample dialyzed in S1, compounding with glycerol to prepare a collagen solution, wherein the collagen solution contains 0.1-2% glycerol and 0.5-1% collagen, stirring well, dispensing into freeze-drying molds, and cross-linking by irradiation; S3: freeze-drying, freeze-drying the gel sample obtained by cross-linking S2, and then packaging and sterilizing by irradiation to prepare a performance-enhanced collagen sponge.

[0007] Preferably, in S1, the collagen raw material is extracted from animal tissues such as bovine Achilles tendon, cowhide, pig skin or fish skin, or is recombinant human collagen.

[0008] Preferably, in S1, the phosphate buffer is obtained by diluting a commercially available PBS solution by 10-100 times, and the dialysis method of the phosphate buffer is: dialysis for 1-4 days, and the solution is changed every 6-12 hours.

[0009] Preferably, in S2, the irradiation is cobalt 60 irradiation or electron beam irradiation, and the irradiation dose is 2-10 kGy.

[0010] Preferably, in S2, the freeze-drying mold is in the shape of a cube, a truncated cone or a cone, and is used to prepare a plug-shaped collagen sponge.

[0011] Preferably, in S3, the irradiation sterilization adopts cobalt 60 irradiation sterilization, electron beam irradiation sterilization or ethylene oxide sterilization.

[0012] The present invention also provides a performance-enhanced collagen sponge prepared by the above preparation method.

[0013] The present invention provides a performance-enhanced collagen sponge and a preparation method thereof, which have the following beneficial effects.

[0014] 1. In the conventional method for preparing collagen, the collagen obtained by extraction and salting out is generally dissolved in dilute acid and then dialyzed. The product of the present invention is directly dialyzed without acid dissolution, and then dialyzed with a low concentration phosphate buffer, which can quickly adjust the pH of the dialyzed solution to neutral, greatly shortening the production cycle of the dialysis process.

[0015] 2. In order to improve the mechanical strength of the product, commercially available collagen sponges generally use a chemical cross-linking process, but this easily makes it difficult for water to enter the material, forming a "dry core" phenomenon, resulting in poor biocompatibility; in contrast, the product of the present invention uses a low-concentration phosphate buffer for dialysis, combined with an irradiation cross-linking process, and while ensuring the mechanical strength of the product, it rehydrates faster, avoids the formation of a "dry core" inside the material, and is conducive to cell growth into the material.

[0016] 3. Adding a certain amount of glycerol to the collagen solution formula before radiation cross-linking of the present invention can avoid shrinkage and deformation of collagen after radiation cross-linking and reduce changes in product size. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a physical picture of the product appearance of the collagen sponge of the present invention (sheet-shaped); Figure 2 This is a physical picture of the product appearance of the collagen sponge of the present invention (plug-shaped); Figure 3 This is a H&E staining photo of the sample of Comparative Example 2 implanted subcutaneously in rats for 4 weeks; Figure 4 This is a H&E staining photograph of the sample of Example 1 implanted subcutaneously in rats for 4 weeks. DETAILED DESCRIPTION

[0018] The present invention is further described below in conjunction with specific embodiments and drawings to help understand the content of the present invention.

[0019] The present invention provides a method for preparing a performance-enhanced collagen sponge, comprising the following steps: S1: Dialysis, dialyzing the collagen raw material with water for injection and phosphate buffer until the pH of the solution reaches above 6.0; the collagen raw material is extracted from animal tissues such as bovine Achilles tendon, cowhide, pig skin or fish skin, or recombinant human collagen. The phosphate buffer is obtained by diluting the commercially available PBS solution 10-100 times, and the dialysis method of the phosphate buffer is: dialysis for 1-4 days, and the solution is changed every 6-12 hours.

[0020] S2: Cross-linking, taking the collagen sample after dialyzation in S1, compounding with glycerol to prepare a collagen solution, the collagen solution contains 0.1-2% glycerol and 0.5-1% collagen, fully stirring, dispensing into freeze-drying molds, and cross-linking by irradiation; the irradiation is cobalt 60 irradiation or electron beam irradiation, and the irradiation dose is 2-10 kGy. The freeze-drying mold is a cube, a truncated cone or a cone, and is used to make a plug-shaped collagen sponge.

[0021] S3: freeze drying, freeze drying the gel sample obtained by cross-linking S2, and sterilizing it by irradiation after packaging to prepare a performance-enhanced collagen sponge. The irradiation sterilization adopts cobalt 60 irradiation sterilization, electron beam irradiation sterilization or ethylene oxide sterilization.

[0022] The present invention also provides a performance-enhanced collagen sponge prepared by the above preparation method.

[0023] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the materials, reagents, etc. used, unless otherwise specified, can be purchased from commercial channels.

[0024] Example 1: A method for preparing bovine collagen sponge Using bovine Achilles tendon as raw material, type I collagen was extracted by digestion with pepsin according to the conventional acid extraction method described in the literature, and collagen precipitate was obtained after salting out. Then, collagen sponge was prepared by the following steps: S1: Dialysis, that is, the collagen precipitate obtained after salt precipitation is placed in a dialysis bag, and first dialyzed with injection water for 3 days, changing the solution every 6 hours; then dialyzed with 0.01× phosphate buffer (i.e., commercially available PBS solution diluted 100 times) for 4 days, changing the solution every 12 hours. At the end of dialysis, the pH of the solution in the dialysis bag reaches above 6.0.

[0025] S2: Cross-linking, i.e. taking the collagen sample after dialysis in the previous step, preparing a collagen solution (mass fraction) according to the following formula: Glycerol 0.1% Collagen 0.5% Water 99.4% The mixture is stirred thoroughly and dispensed into freeze-drying molds, and then cross-linked by irradiation with cobalt 60 at a dose of 2 kGy. If the freeze-drying mold is designed to be a cube, a truncated cone or a cone, a plug-shaped collagen sponge can be prepared.

[0026] S3: freeze drying, i.e. placing the gel sample obtained by cross-linking in the previous step in a vacuum freeze dryer for freeze drying until it is completely freeze dried.

[0027] The freeze-dried sponge sample in the previous step is cut into the required size and specifications, and then sterilized by cobalt 60 irradiation after packaging to obtain the performance-enhanced collagen sponge. Figure 1 and Figure 2 .

[0028] Example 2: A method for preparing a porcine collagen sponge Using pig skin as raw material, type I collagen was extracted by digestion with pepsin according to the conventional acid extraction method described in the literature, and collagen precipitate was obtained after salting out. Then, the following steps were used to prepare collagen sponge: S1: Dialysis, that is, the collagen precipitate obtained after salt precipitation is placed in a dialysis bag, and first dialyzed with injection water for 7 days, changing the solution every 12 hours; then dialyzed with 0.1× phosphate buffer (i.e., commercially available PBS solution diluted 10 times) for 1 day, changing the solution every 6 hours. At the end of dialysis, the pH of the solution in the dialysis bag reaches above 6.0.

[0029] S2: Cross-linking, i.e. taking the collagen sample after dialysis in the previous step, preparing a collagen solution (mass fraction) according to the following formula: Glycerin 2% Collagen 1% Water 97% The mixture was stirred thoroughly and evenly, divided into freeze-drying molds, and then cross-linked by electron beam irradiation at a dose of 10 kGy.

[0030] S3: freeze drying, i.e. placing the gel sample obtained by cross-linking in the previous step in a vacuum freeze dryer for freeze drying until it is completely freeze dried.

[0031] The freeze-dried sponge sample in the previous step is cut into required sizes and specifications, and then sterilized with ethylene oxide after packaging to obtain a finished product of porcine collagen sponge.

[0032] Example 3: A method for preparing a recombinant human collagen sponge Commercially available recombinant human type III collagen was used as a raw material, a collagen solution was prepared by using dilute acid, and a collagen precipitate was obtained after salting out. Then, a collagen sponge was prepared by the following steps: S1: Dialysis, that is, the collagen precipitate obtained after salt precipitation is placed in a dialysis bag, and first dialyzed with injection water for 5 days, changing the solution every 8 hours; then dialyzed with 0.05× phosphate buffer (i.e., commercially available PBS solution diluted 20 times) for 3 days, changing the solution every 8 hours. At the end of dialysis, the pH of the solution in the dialysis bag reaches above 6.0.

[0033] S2: Cross-linking, i.e. taking the collagen sample after dialysis in the previous step, preparing a collagen solution (mass fraction) according to the following formula: Glycerin 1% Collagen 0.7% Water 98.3% The mixture was stirred thoroughly and evenly, divided into freeze-drying molds, and then cross-linked by cobalt 60 irradiation with an irradiation dose of 6 kGy.

[0034] S3: freeze drying, i.e. placing the gel sample obtained by cross-linking in the previous step in a vacuum freeze dryer for freeze drying until it is completely freeze dried.

[0035] The freeze-dried sponge sample in the previous step is cut into required sizes and specifications, and then packaged and sterilized by electron beam irradiation to obtain a finished recombinant human collagen sponge.

[0036] Comparative Example 1: Preparation and performance comparison of collagen sponges using different dialysis processes Preparation and pH test of samples in Comparative Example 1: Collagen sponge was prepared by traditional dialysis process, that is, the collagen precipitate obtained after salting out was put into dialysis bag, first dialyzed with 0.6% acetic acid solution for 3 days to fully dissolve the collagen precipitate, and then dialyzed with water for injection. The solution was changed every 8 hours, and the pH of the sample in the dialysis bag was monitored every day. The results showed that the average pH of the sample was 3.6±0.3 and 5.1±0.2 at 7 and 14 days of dialysis. Samples were taken at 7 and 14 days of dialysis, and performance-enhanced collagen sponges were prepared according to the methods described in steps S2 and S3 of Example 1, respectively. The pH of the product was measured according to the method described in the industry standard "YY / T 1511-2017 Collagen Sponge". The results showed that the pH of the collagen sponges prepared by sampling at 7 and 14 days of dialysis were 3.8±0.2 and 5.1±0.3, respectively. The sample prepared at 7 days of dialysis did not meet the pH requirement of 4.0-7.0 in "YY / T 1511-2017 Collagen Sponge".

[0037] pH test of samples in Example 1: The collagen precipitate was dialyzed using the dialysis method described in step S1 of Example 1. Three batches of samples were processed, and the pH of the samples in the dialysis bag was measured at the end of the dialysis. The results showed that the average pH value of the three batches of samples at the end of the dialysis was 6.7±0.2. The pH of the finished product was measured according to the method described in the industry standard "YY / T 1511-2017 Collagen Sponge", and the result was 6.3±0.2, which met the pH requirement of 4.0-7.0 in "YY / T 1511-2017 Collagen Sponge".

[0038] The above tests show that compared with the traditional method of first dissolving with acid and then dialyzing, the present invention directly dialyzes the collagen precipitate after salting out without acid dissolution, and subsequently uses a low concentration phosphate buffer for dialysis, which can quickly adjust the pH value of the dialysis solution to neutral, greatly shortening the production cycle of the dialysis process.

[0039] Comparative Example 2: Preparation of chemically cross-linked collagen sponge The dialysis and freeze-drying steps described in Example 1 were used, and the radiation cross-linking was replaced by chemical cross-linking, that is: bovine Achilles tendon was used as raw material, type I collagen was extracted according to the conventional acid method described in the literature, and collagen precipitate was obtained after salting out, and then the collagen sponge was prepared by the following steps: S1: Dialysis, that is, the collagen precipitate obtained after salting out is placed in a dialysis bag, and first dialyzed with injection water for 3 days, changing the solution every 6 hours; then dialyzed with 0.01× phosphate buffer (i.e., commercially available PBS solution diluted 100 times) for 4 days, changing the solution every 12 hours.

[0040] S2: freeze-drying, i.e., the gel sample obtained by dialysis in the previous step is added with water to form a 0.5% collagen solution, which is fully stirred and dispensed into freeze-drying molds, and placed in a vacuum freeze dryer for freeze drying until completely freeze-dried.

[0041] S3: Chemical cross-linking, i.e. taking the freeze-dried collagen sponge sample from the previous step, placing it in a cross-linking solution containing 0.019% 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 0.0058% N-hydroxysuccinimide for cross-linking at 4°C for 24 hours, then taking out the sample and washing it thoroughly with PBS solution to remove the cross-linking agent residue, placing it in a vacuum freeze dryer for freeze-drying again, cutting it into the required model and specifications after freeze-drying, packaging it, and sterilizing it by cobalt 60 irradiation to obtain the finished chemically cross-linked collagen sponge product.

[0042] Comparative Example 3: Preparation of collagen sponge without glycerol addition Only the collagen solution formula in the "cross-linking" step of Example 1 was adjusted to contain only 0.5% collagen, that is, the glycerol component was deleted, and the remaining steps were the same as Example 1, and the appearance of the samples during the preparation process was observed. It was found that compared with the collagen sponge prepared in Example 1, the sample of Comparative Example 3 underwent obvious shrinkage and deformation after irradiation cross-linking, and a large amount of water was precipitated. After freeze-drying, the surface of the sample was uneven. Therefore, it can be concluded that the addition of glycerol can reduce the deformation degree of the sample after irradiation cross-linking to a certain extent.

[0043] Performance test: Comparative test of rehydration performance and subcutaneous implantation test Rehydration performance test: Take the samples prepared in Example 1, Comparative Example 1 (dialysis for 14 days) and Comparative Example 2, cut them into 1 cm × 1 cm squares respectively, measure the initial thickness of the samples, place them in physiological saline, and observe them until the samples are completely rehydrated and all become translucent (the color of the unrehydrated particles is white), and record the time required for complete rehydration; then take out the samples, gently press and squeeze out the water in the materials, and rehydrate them again, repeat this process 50 times, and finally put the samples into physiological saline for full rehydration, take out the test sample thickness and calculate the thickness change rate according to the following formula: Thickness change rate = (thickness before rehydration - thickness after rehydration) / thickness before rehydration The experimental results show that the rehydration time of the samples prepared in Example 1 and Comparative Example 1 is 50 s and 820 s, respectively, while the sample in Comparative Example 2 cannot be completely infiltrated after being immersed in physiological saline for 24 hours, and there is a "dry core" phenomenon inside the material, which indicates that the present invention uses low-concentration phosphate buffer for dialysis, combined with the radiation cross-linking process, compared with the chemical cross-linking process, it can achieve faster rehydration and avoid the formation of a "dry core" inside the material. In addition, after 50 reciprocating extrusions, the thickness change rates of the samples prepared in Example 1, Comparative Example 1 (dialysis for 14 days) and Comparative Example 2 are 5.3%, 16.7% and 4.9%, respectively, which indicates that the present invention uses low-concentration phosphate buffer for dialysis, which can improve the mechanical support and resilience of the material, reduce the deformation of the material after external extrusion (5.3% vs. 16.7%), and the combination of the radiation cross-linking process can achieve the mechanical property improvement effect equivalent to the EDC / NHS chemical cross-linking process (5.3% vs. 4.9%).

[0044] Subcutaneous implantation animal experiment in rats: According to the method described in "GB / T16886.6-2022 Biological Evaluation of Medical Devices Part 6: Local Reaction Test after Implantation", the local reactions of the samples prepared in Example 1 and Comparative Example 2 to subcutaneous implantation in SD rats were evaluated. The test results showed that after 4 weeks of subcutaneous implantation in rats, few cells infiltrated into the material in the sample group of Comparative Example 2, and only a small number of cells adhered to the surface or shallow layer of the material. Figure 3 As shown in the figure, this may be due to the chemical cross-linking that increases the hydrophobicity of the material, makes it slow to absorb water and easy to "dry the core", and causes poor biocompatibility; while in the material of the sample of Example 1, more fibroblasts can be seen infiltrating inside the material, and new blood vessels are generated, such as Figure 4 As shown, this shows that compared with chemically cross-linked collagen sponges, the product of the present invention is more conducive to the growth of cells and tissues into the material, and is easier for the material to integrate with autologous tissues and achieve tissue remodeling. In addition, the dissection found that the material was still visible at the implantation site 8 weeks after implantation, indicating that the radiation cross-linking process can delay the degradation of collagen sponges in the body.

[0045] The present invention adopts an optimized dialysis process to prepare a collagen gel matrix, compound glycerol to form a homogeneous solution system, then utilizes radiation to induce a molecular cross-linking reaction, and finally combines with freeze-drying molding technology to successfully prepare a collagen sponge material with enhanced mechanical properties and water absorption characteristics. The product of the present invention is directly dialyzed without acid dissolution, and subsequently dialyzed with a low-concentration phosphate buffer solution, which can quickly adjust the pH value of the dialysis solution to neutrality, greatly shortening the production cycle of the dialysis process; in addition, low-concentration phosphate buffer solution is used for dialysis, combined with an irradiation cross-linking process, and while ensuring the mechanical strength of the product, its rehydration is faster, avoiding the formation of a "dry core" inside the material, which is conducive to the growth of cells into the material; adding a certain amount of glycerol to the formula of the collagen solution before irradiation cross-linking can avoid the shrinkage and deformation of the collagen after irradiation cross-linking and reduce the change in product size.

[0046] The invention concept is described in detail using specific examples herein, and the description of the above embodiments is only used to help understand the core idea of ​​the invention. It should be pointed out that any obvious modification, equivalent substitution or other improvement made by a person of ordinary skill in the art without departing from the invention concept should be included in the protection scope of the present invention.

Claims

1. A method for preparing a performance-enhanced collagen sponge, characterized in that: The steps include: S1: Dialysis: dialyze the collagen raw material using water for injection and phosphate buffer until the pH of the solution reaches above 6.0; S2: cross-linking, taking the collagen sample dialyzed in S1, compounding with glycerol to prepare a collagen solution, wherein the collagen solution contains 0.1-2% glycerol and 0.5-1% collagen, stirring well, dispensing into freeze-drying molds, and cross-linking by irradiation; S3: freeze-drying, freeze-drying the gel sample obtained by cross-linking S2, and then sterilizing it by irradiation to prepare a performance-enhanced collagen sponge.

2. The method for preparing a performance-enhanced collagen sponge according to claim 1, characterized in that: In S1, the collagen raw material is extracted from animal tissues such as bovine Achilles tendon, cowhide, pig skin or fish skin, or recombinant human collagen.

3. The method for preparing a performance-enhanced collagen sponge according to claim 2, characterized in that: In S1, the phosphate buffer solution is obtained by diluting a commercially available PBS solution by 10-100 times, and the dialysis method of the phosphate buffer solution is: dialysis for 1-4 days, and the solution is changed every 6-12 hours.

4. The method for preparing a performance-enhanced collagen sponge according to claim 3, characterized in that: In S2, the irradiation is cobalt 60 irradiation or electron beam irradiation, and the irradiation dose is 2-10 kGy.

5. The method for preparing a performance-enhanced collagen sponge according to claim 4, characterized in that: In S2, the freeze-drying mold is in the shape of a cube, a truncated cone or a cone, and is used to prepare a plug-shaped collagen sponge.

6. The method for preparing a performance-enhanced collagen sponge according to claim 5, characterized in that: In S3, the irradiation sterilization adopts cobalt 60 irradiation sterilization, electron beam irradiation sterilization or ethylene oxide sterilization.

7. A performance-enhanced collagen sponge prepared by the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Preparation method of collagen sponge

    CN104645403A

  • Modified bio-based hemostatic composite collagen sponge as well as preparation method and application thereof

    CN117919484A

  • Double-layer collagen sponge as well as preparation method and application thereof

    CN118772481A

  • Crosslinked recombinant collagen as well as preparation method and application thereof

    CN118994372A

  • Collagenic material useful in particular for preventing post-operative adhesions

    US20010008930A1